PENGEMBANGAN INSTRUMEN PENILAIAN KEMAMPUAN BERPIKIR KREATIF DALAM KEWIRAUSAHAAN PADA MATERI BIOTEKNOLOGI SMA BERBASIS KREAFY - Ade Nikmah Latifiani; Wahyu Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to develop an assessment instrument for creative thinking skills integrated with entrepreneurial values in biotechnology learning for senior high school students, based on the Kreafy application. The research employed a Research and Development (R&D) method using the Borg and Gall development model. The creative thinking assessment instrument in entrepreneurship on biotechnology materials consisted of four creativity indicators, namely flexibility, originality, fluency, and elaboration. The research subjects were eleventh-grade senior high school students. The results showed that the creative thinking assessment instrument in entrepreneurship met the criteria of content validity and construct validity based on evaluations by subject-matter experts, instrument experts, and media experts. The reliability analysis using Cronbach’s alpha in the large-scale trial indicated a high reliability coefficient of 0.898. Item analysis revealed that the instrument had proportional discrimination indices and difficulty levels. The creativity profile of students at Beqi Senior High School showed that 29% of students were categorized as “very creative,” 53% as “creative,” and 18% as “moderately creative.” The creativity indicator with the highest percentage was elaboration (76%), while originality obtained the lowest percentage (70%). The development of this creativity assessment instrument was complemented by a user guidebook to facilitate teachers in operating the Kreafy application, which contains the assessment instrument for creative thinking skills in entrepreneurship on biotechnology materials for senior high school students.